Understanding the Acceptance Intention for Consumers toward Using E-VAT (Value-Added Tax) Refund System - Chen, Yue-Yang; Lee, Liang-Cheng; Lee, Wen-Huai; Phuc, Tran Thi Hong (RA Journal Of Applied Research, 2022)
Electronic tax or value-added tax (VAT) refund system is a computerized tax administration system that is especially designed to handle general tax administration from registration, assessment, filing returns and processing of claims and refunds. This study was conducted with the aim to develop a model of factors influencing the intention to use the electronic value-added return tax refund system and the impact of these factors on the intention toward using the system. It provides solutions to encourage enterprises to use when the system is officially deployed. Specifically, this research tried to predict the intention of the taxpayer's interest in using the electronic value added tax refund system by applying Technology Acceptance Model (TAM). This research takes the taxpayers in Dong Nai tax department in Vietnam as the samples with total of 196 respondents. Data were analyzed using Structural Equation Modeling (SEM) which consists of two stages: the measurement model (measurement model) and the structural model. The research finds that the perceive ease of use has a significant positive effect on perceived usefulness, attitude, and intention to use electronic value added tax refund system. In addition, the path from perceived usefulness to attitude and to intention are also supported. Finally, the path from attitude to intention is also supported.